Konsep Kehidupan Menurut Perspektif Al-Quran - Muhammad Iqbal (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Life if it is based on humans (sense creatures) does not apply to animals and plants is a process where humans collect good deeds before they return to Allah swt. or it can also be said that this life is a field and the harvest is called a reward. So, the quality of a person's faith depends on the number of results / good deeds obtained while in the world. Allah swt has created various types of living creatures on this earth with a clear purpose, namely to worship Him, as Allah says in Surah al-Dzariat verse 56. It Means: “And I did not create the jinn and humans except that they might serve Me” Maybe some body ask what is the meaning of life? If we look closely, there will be a lot of answers to this one question. Some answered that life is money, so first of life they are looking for money. This means that if he does not have money, it is as if his life has been lost. Others answered, that life is a position. So the first of life is a position. The approach used in writing this article is a qualitative approach, with the type of research library research, and the data collection method used by the author is documentation, so that the books obtained come from the study of texts or books that are relevant to the main formulation of the problem. According to the author, the reason for raising this title is so that readers can know what God's purpose is. created humans to live and can also add insight that this life is not eternal, but mortal. Indeed, eternal life is in the hereafter when Allah takes the life, we know the meaning of life according to the contents of this article, hopefully this article can have a positive impact on the reader so that this life becomes useful by always hoping for His pleasure.